Anticipated stigma and medication adherence among people living with HIV: the mechanistic roles of medication support and ART self-efficacy. Issue 8 (2nd August 2020) - Zeng, Chengbo; Li, Xiaoming; Qiao, Shan; Yang, Xueying; Shen, Zhiyong; Zhou, Yuejiao
ABSTRACT: This study aimed to examine the relationship between anticipated stigma and medication adherence as well as the mechanistic roles of medication support and ART self-efficacy. Data were derived from the baseline assessment of a prospective cohort study in Guangxi, China. A total of 1198 PLWH were recruited and assessed on their sociodemographic characteristics, medication adherence, anticipated stigma, medication support, and ART self-efficacy. Path analysis was used to examine the direct effect from anticipated stigma to medication adherence and indirect effects through medication support and ART self-efficacy. Path model revealed that the indirect effect from anticipated stigma to medication adherence was statistically significant while the direct effect was not significant. Anticipated stigma could influence medication adherence through ART self-efficacy but not through medication support. The serial mediating effect of medication support and ART self-efficacy on the relationship between anticipated stigma and medication adherence was significant. Anticipated stigma affects medication adherence among PLWH through its adverse impact on medication support and ART self-efficacy. Tailored interventions promoting medication support and ART self-efficacy may alleviate the negative influence of anticipated stigma on medication adherence among PLWH. Additionally, policy efforts aiming to reduce stigma against PLWH and increasing medication support are warranted to improve medication adherence among PLWH.